Practice-Changing Perspectives regarding Systemic Therapy in Early Breast Cancer: Opinions of German Experts regarding the 17th St. Gallen International Consensus Conference - Kolberg-Liedtke, Cornelia; Lueftner, Diana; Brucker, Sara Y.; Budach, Wilfried; Denkert, Carsten; Fasching, Peter; Haidinger, Renate; Harbeck, Nadia; Huober, Jens; Jackisch, Christian; Janni, Wolfgang; Krug, David; et al. (Breast Care, 2022)
The general topic of this year's 17th St. Gallen (SG) International Consensus Conference on the treatment of patients with early breast cancer (SG-BCC) was "Customizing local and systemic therapies for women with early breast cancer. " This topic considers that each treatment decision must also consider the cancer-specific situation of the individual patient. This year, the votes of the SG-BCC were again discussed taking into account the multidisciplinary German S3 Guidelines and the recommendations of the Breast Cancer Working Group of the AGO (Arbeitsgemeinschaft Gynakologische Onkologie; AGO Mamma). As the international panel of the SG-BCC consists of experts from different countries, the votes do represent an international cross-section of opinions. Therefore, it is useful to discuss the voting results with respect to the German evidence-based treatment guidelines. This publication focuses mainly on systemic treatment.
CRIS-Team WoS Importer:2022-06-17